2020
DOI: 10.1029/2020gl088033
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Mixing in a Loop Current Eddy From Glider‐Based Microstructure Observations

Abstract: Turbulence parameters have been estimated from microstructure velocity and temperature measurements in an anticyclonic Loop Current Eddy in the Gulf of Mexico for the very first time. Measurements were performed during a mission in October 2016, using a G2 Webb Research Slocum ocean glider instrumented with a microstructure sensors suite. Well‐defined turbulent kinetic energy dissipation rate patterns in the eddy and the surface mixed layer were clearly identified from both the velocity and temperature microst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
(51 reference statements)
1
3
1
Order By: Relevance
“…In fact, energy loss of LCRs through relative wind work and energy transfer from APE to KE through Ekman buoyancy fluxes are to be expected for a mesoscale eddy subject to wind forcing [51], and are currently under investigation. However, our simple scaling of the order of magnitude of an equivalent energy dissipation rate ϵ is in good agreement with values observed in the GoM [42,43].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In fact, energy loss of LCRs through relative wind work and energy transfer from APE to KE through Ekman buoyancy fluxes are to be expected for a mesoscale eddy subject to wind forcing [51], and are currently under investigation. However, our simple scaling of the order of magnitude of an equivalent energy dissipation rate ϵ is in good agreement with values observed in the GoM [42,43].…”
Section: Discussionsupporting
confidence: 89%
“…We explore three different hypothesis: (a) energy is homogeneously dissipated within the whole GoM's volume; (b) energy is dissipated within the top 1000 m; (c) energy is dissipated within the top 500 m. The necessary dissipation rate is respectively of 1.8, 4.5, and 9.0 ×10 −10 W kg −1 . These values are lower than direct microstructure measurements in the vicinity of LCRs by Molodstov et al's [42] ([10 −9 − 10 −8 ] W kg −1 ), but are consistent with their GoM's background values [10 −10 − 10 −9 ] W kg −1 , as well as Whalen et al's [43] estimates between 250 and 500 m, using fine-scale strain parameterization (≈ 5 × 10 −10 W kg −1 ).…”
Section: Heat Salt and Energy Statistical Propertiescontrasting
confidence: 55%
“…Note also that, while the resolution of our relocated observations does not resolve sub-mesoscale frontal processes, such as symmetric instability [51], the latter were shown to occur in other mesoscale eddies [52][53][54][55] and could also occur in LCRs and contribute to the mixing of their tracers. Finally, the occurrence of layering at the periphery of the sampled LCR [11], associated with elevated mixing [12] might also act in eroding the tracer anomalies, and contribute to the decay of the eddy, as observed in intra-thermocline lenses in the North Atlantic [37].…”
Section: The Lcr's Vertical Structurementioning
confidence: 98%
“…During the past two decades, gliders (autonomous underwater vehicles) have become widespread, reliable, flexible, and cost-effective measurement platforms [1][2][3][4]. They were shown to be appropriate for measuring most oceanic features and processes on a variety of time and space scales, including high-frequency internal waves [5], intense surface boundary currents [6], mesoscale and submesoscale eddies [7][8][9][10], fine-scale thermohaline stirring [11], or turbulent mixing [12].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, direct observations of three anticyclonic eddies in the South China Sea demonstrated that turbulent mixing is considerably higher at the edge than the center (Yang et al 2017). Recently, gilder‐based microstructure observations confirmed that the turbulent kinetic energy dissipation rates are higher at the eddy edge than the core in an anticyclonic eddy in the Gulf of Mexico (Molodtsov et al 2020). Thus, elevated turbulent mixing at the edge of an anticyclonic eddy may be primarily attributed to submesoscale processes (Yang et al 2017).…”
Section: Discussionmentioning
confidence: 93%